A New Bayesian Solution to the Paradox of the Ravens. Issue 1 (January 2014) - Rinard, Susanna
Abstract : The canonical Bayesian solution to the ravens paradox faces a problem: it entails that black nonravens disconfirm the hypothesis that all ravens are black. I provide a new solution that avoids this problem. On my solution, black ravens confirm that all ravens are black, while nonblack nonravens and black nonravens are neutral. My approach is grounded in certain relations of epistemic dependence, which, in turn, are grounded in the fact that the kind raven is more natural than the kind black . The solution applies to any generalization "All F's are G" in which F is more natural than G .